OPPORTUNITIES AND CHALLENGES OF HOME-GROWN SCHOOL FEEDING PROGRAMME: A CASE OF WESTERN PROVINCE, ZAMBIA - Sitali, Constance (International Journal of Research -GRANTHAALAYAH, 2021)
Home-grown school feeding (HGSF) is an innovative approach to school meals that encourages school to source nutritious food from local smallholder farmers. Therefore, the purpose of this study was to find out the opportunities and challenges of Home-grown school feeding in Western Province of Zambia. The study was guided by the theory of change by Weiss. Being a qualitative study, descriptive approach was used as a design. A total of 81 informants were targeted; 10 headteachers and 30 teachers from 10 public primary schools, 40 selected smallholder farmers from communities around schools and WFP Provincial Officer. Purposive sampling procedure was used to select the informants as they were directly involved in the school feeding while simple random sampling was used to select 10 public primary schools in 5 districts. The instruments used for data collection were semi-structured questionnaires and face to face interview guide. Qualitative data obtained were transcribed, analysed thematically and presented descriptively with verbatim quotes. The study revealed that HGSF has several opportunities, namely; equitable access to education, foster local economic, stimulating agriculture growth, food security and nutritious foods, diversification of local production, job creation, access to additional market and capacity building among others. Further, despite multiple opportunities, the study was characterized by some challenges such as climate change resulting in an unpredictable weather pattern, inconsistency in supply of food to schools, frequent rise of food prices affecting household food access, low level of agriculture technology and high dependency on rainfall for farming activities, the use of centralised approach to procurement of food, price volatility and unpredictable markets, lack of infrastructure and water scarcity. The study recommended that the Government should put in place a set of mechanisms that assist smallholder farmers in applying good agricultural practices and enhance their adaptability to climate change.